Deposition of Copper Nanofilms by Surface-Limited Redox Replacement of Underpotentially Deposited Lead on Polycrystalline Gold. Issue 1 (7th August 2018) - Dornhof, Johannes; Urban, Gerald A.; Kieninger, Jochen
Abstract : Electrochemical atomic layer deposition (E-ALD) of copper on polycrystalline gold is a promising method to achieve highly reproducible nanofilms. Cu films of more than 30 nm were deposited by the repetitive execution of underpotential deposition (UPD) of lead and a subsequent surface limited redox replacement by Cu. Both steps were carried out in the same solution. The method enables, in contrast to conventional gas phase ALD, the deposition of layers with different height on the same substrate. Deposit growth in this one-pot system was monitored in-situ with an electrochemical quartz crystal microbalance. Film thickness, measured by optical profilometry, was compared to the number of deposition cycles and indicated a highly linear dependency. Obtained layers were characterized by means of atomic force and scanning electron microscopy and showed a slight roughening with almost no increase in the effective surface area. Energy dispersive X-ray measurements confirmed the purity of deposited Cu nanofilms. It was shown, that even with a simple setup, the described method allows the reproducible deposition of Cu on polycrystalline Au.